PENGARUH GELOMBANG MIKRO DAN SULFUR SEBAGAI AGEN PASIVASI TERHADAP SPEKTRUM ABSORBANSI KARBON DOTS BERBASIS BAN BEKAS - Ananda Tira Septiana Sari; Ety Jumiati; Miftahul Husnah (Universitas Riau, 2023)
Used tires that are not used are usually thrown away and cause damage and environmental pollution. Information on the use of used tires is still limited, used tires are usually used in the synthesis of nanomaterials such as in the field of nanotechnology. This research was conducted to determine whether carbon dots can be synthesized from used car tires, sulfur can be used as a passivation agent in the synthesis of carbon dots, and to determine the wave absorption and fluorescence of carbon dots synthesized purely and with the addition of a passivation agent.Sulfur was used as a passivation agent with a carbon and sulfur ratio of 1:1. Microwave time variations were used 30, 35, and 40 minutes. The UV-Vis characterization of carbon dots showed a higher absorbance with variations in the length of microwave time and the addition of passivation agents. Luminance analysis with UV lamp obtained a brighter glow on karbon dots with the addition of a passivation agent.